2020
DOI: 10.3390/w12082304
|View full text |Cite
|
Sign up to set email alerts
|

A Quantile Mapping Method to Fill in Discontinued Daily Precipitation Time Series

Abstract: We present and assess a method to estimate missing values in daily precipitation time series for the Mediterranean island of Crete. The method involves a quantile mapping methodology originally developed for the bias correction of climate models’ output. The overall methodology is based on a two-step procedure: (a) assessment of missing values from nearby stations and (b) adjustment of the biases in the probability density function of the filled values towards the existing data of the target. The methodology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…In this study, we used the name "empirical quantile mapping plus (EQM + )" to refer to the empirical quantile mapping applied to the outputs (values estimated by all six techniques). e study [31] obtained a better result (reduced mean absolute error) after applying quantile mapping on the outputs generated by other techniques. us, we applied it to evaluate its performance on the outputs obtained by other techniques.…”
Section: Empirical Quantile Mapping Plus (Eqm +mentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we used the name "empirical quantile mapping plus (EQM + )" to refer to the empirical quantile mapping applied to the outputs (values estimated by all six techniques). e study [31] obtained a better result (reduced mean absolute error) after applying quantile mapping on the outputs generated by other techniques. us, we applied it to evaluate its performance on the outputs obtained by other techniques.…”
Section: Empirical Quantile Mapping Plus (Eqm +mentioning
confidence: 91%
“…e best performance of the machine learning process was stated for ANN [26,27], ordinary kriging [28,29], and Kernel approaches [30]. Besides, Grillakis et al [31] indicated the acceptable performance of empirical quantile mapping in filling the discontinued daily rainfall data in the Mediterranean island of Crete.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to previous research related to the filling of daily missing data by means of statistical methods (e.g., [27,[46][47][48][49][50]), our results have indicated slightly larger values of RMSE and MAE, but moderately lower values for CC, particularly for the MLR approach; of course, the distinct climate conditions, which drive the alternation between wet and dry states, as well as the occurrence of large rainfall amounts, may render this direct comparison unfair across different geographic regions. On the other hand, one should note that, in most studies, the filling procedures are applied to relatively shorter periods (i.e., less than a full water year), or in more densely gauged areas, in which a better description of the rainfall fields is possible.…”
Section: Daily Estimatesmentioning
confidence: 99%
“…The QM method effectively eliminates model bias, not only for mean and interannual variability but also for extreme events 24 , 29 31 . The QM bias correction method has also been developed and applied to the climate change impact studies in Italy 32 and Sweden 30 and was used to fill in missing climate data 33 .…”
Section: Introductionmentioning
confidence: 99%